Transformation Cabinet to meet people's aspirations - Borneo Post, (KK) (Borneo Post (KK), 2013)
KUALA LUMPUR: After fielding a 'transformation' team in the 13th general election (GE13),Prime Minister Datuk Seri Najib Tun Razak is expected to form a 'transformation' Cabinet.